Strategic Plan to Enhance Employee Wellbeing at Karen Women Empowerment Group - Nwe Ni, Win; Fernando, Maria Socorro; Pupat, Nathaya (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Humanitarian workers in Myanmar face unprecedented challenges as they navigate the complexities of a political crisis and ongoing conflict. These individuals endure significant physical and psychological harm due to the unstable environment, which is marked by civil unrest and limited access to vulnerable populations. This study aims to explore the employee well-being of the Karen Women Empowerment Group (KWEG) staff and to develop a long-term strategy to enhance their well-being through initiatives in Organizational Support, Leadership, and Effective Coping Mechanisms. The research has three main objectives: 1) To evaluate the current coping strategies and support systems available to employees that enhance the employee wellbeing at KWEG; 2) To gather employee insights on wellbeing support, current and preferred to enhance employee wellbeing at KWEG; and 3) to design strategies that enhance employee wellbeing based on the findings. The research questions, which focus on employee well-being at KWEG, were developed using the Appreciative Inquiry (AI) model. Purposive sampling was employed to select participants for the qualitative research, ensuring the inclusion of eight informants with relevant experiences or characteristics to address the research objectives effectively. Two virtual focus group discussions, each consisting of four participants, were conducted to gather in-depth insights and create a collaborative space for all informants to contribute meaningfully. The results reveal that KWEG staff envision a positive workplace culture, which can be achieved by promoting mutual respect, understanding, and support among colleagues. This culture should be complemented by supportive leadership that encourages employees to express their needs freely, fosters appreciation and trust, cultivates empathy, and implements effective coping strategies. Key strategies identified include flexible working hours, regular team outings, psychosocial counseling sessions, a reassurance policy for staff health, and the cultivation of a positive working environment.